NOTEPAD ANDROID APPLICATION WITH BIOMETRIC FINGERPRINT LOCK (NOTEY) - Emmaryna, Irie (Universiti Malaysia Sarawak (UNIMAS), 2019)
This paper is to develop a notepad Android application with biometric fingerprint lock. Biometric lock within applications in mobile devices is the latest security features that operates with the hardware that can scan the biometric of a person in order to access a confidential information. There are some applications that has implemented biometric lock, and among the listed are notepad application. This paper describes the evaluation of security of biometric lock on the notepad application as well as developing a notepad application embedding biometric lock in it.